Pectolinarin inhibits proliferation, induces apoptosis, and suppresses inflammation in rheumatoid arthritis fibroblast‐like synoviocytes by inactivating the phosphatidylinositol 3 kinase/protein kinase B pathway. Issue 9 (24th April 2019) - Wang, Laifang; Wang, Na; Zhao, Qing; Zhang, Bingyi; Ding, Yanjie
Abstract: Rheumatoid arthritis fibroblast‐like synoviocytes (RA‐FLSs), a pathological hallmark of rheumatoid arthritis (RA), exhibit the characteristics of tumor cells. The extracts of Cirsium japonicum var. ussuriense have been shown to possess antitumor and anti‐inflammatory activities. Our study aimed to investigate the effects of pectolinarin, a flavonoid compound isolated from C. japonicum var. ussuriense, on RA. Cell viability was evaluated by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl‐tetrazolium bromide assay. Apoptosis was determined by flow cytometry analysis and Western blot analysis of Bax and Bcl‐2 levels. Inflammation was assessed by detecting the expressions and secretion of interleukin (IL)‐6 and IL‐8 using quantitative real‐time polymerase chain reaction and enzyme‐linked immunosorbent assay, respectively. The production of nitric oxide (NO) and prostaglandin E2 (PGE2) was also measured. The effects of pectolinarin on the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) pathway were examined by Western blot. We found that pectolinarin significantly inhibited cell viability at 24 and 48 hours in a dose‐dependently manner in RA‐FLSs. Pectolinarin reduced the apoptotic rate, increased Bax level, and decreased Bcl‐2 level in RA‐FLSs. Pectolinarin inhibited the messenger RNA expression and secretion of IL‐6 and IL‐8, as well as the production of PGE2 and NO in RA‐FLSs. Furthermore, pectolinarin inactivated the phosphatidylinositol 3 kinase/protein kinase B (PI3K/Akt) pathway in RA‐FLSs. Activation of the PI3K/Akt pathway by 740Y‐P impaired the effects of pectolinarin on cell viability, apoptosis, and inflammation in RA‐FLSs. In conclusion, pectolinarin suppressed cell proliferation and inflammatory response and induced apoptosis in RA‐FLSs via inactivation of the PI3K/Akt pathway. Abstract : We provided the first evidence that pectolinarin suppressed cell proliferation and inflammatory response, and induced apoptosis in Rheumatoid arthritis fibroblast‐like synoviocytes via inactivation of the phosphatidylinositol 3 kinase/protein kinase B pathway, providing novel insights into the biological activity of pectolinarin in rheumatoid arthritis (RA) pathogenesis. Our study suggested that pectolinarin may be a promising therapeutic candidate for RA therapy.